2008
DOI: 10.1158/1078-0432.ccr-07-4528
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and Cytoplasmic Expression of ERβ1, ERβ2, and ERβ5 Identifies Distinct Prognostic Outcome for Breast Cancer Patients

Abstract: Purpose: Previous conflicting results about the prognostic significance of estrogen receptor (ER)-h in breast cancer may be explained by contribution of isoforms, of which five exist. Our aim was to elucidate the prognostic significance of ERh1, ERh2, and ERh5 by immunohistochemistry in a large cohort of breast carcinomas with long-term follow-up. Experimental Design: Tissue microarrays were stained with ERh1, ERh2, and ERh5 antibodies and scored as percentage of positive tumor cells and using the Allred syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
126
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(132 citation statements)
references
References 45 publications
4
126
0
Order By: Relevance
“…Correlations between S105-ER␤ expression and ER␣ (P Ͻ 0.0001) and low tumor grade (P Ͻ 0.015) were observed in the tamoxifensensitive but not the tamoxifen-resistant cohort (Table 1). 6 In the combined dataset significant correlations were observed with ER␣ (P Ͻ 0.0001) and low grade (P ϭ 0.015) with PR showing a trend toward significance (P ϭ 0.05). No significant correlation of S105-ER␤ expression with age, tumor size, PR, and AR expression was observed.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Correlations between S105-ER␤ expression and ER␣ (P Ͻ 0.0001) and low tumor grade (P Ͻ 0.015) were observed in the tamoxifensensitive but not the tamoxifen-resistant cohort (Table 1). 6 In the combined dataset significant correlations were observed with ER␣ (P Ͻ 0.0001) and low grade (P ϭ 0.015) with PR showing a trend toward significance (P ϭ 0.05). No significant correlation of S105-ER␤ expression with age, tumor size, PR, and AR expression was observed.…”
mentioning
confidence: 87%
“…Recent reports have outlined the importance of specific ER␤ isoforms in defining clinical outcome. [5][6][7] This study has showed that the added presence of S105-ER␤ can further stratify patients, potentially allowing more precise selection of patient subgroups that will derive optimum benefit from endocrine therapy. Although ER␣ and ER␤ reside on separate genes, 1 they are related molecules and our observation with S105-ER␤ is in line with some but not all studies relating ER␣ phosphorylation with better clinical outcome.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Generally, higher levels of ERb-like expression were found associated with the expression of good prognostic markers or better clinical outcome, usually in patients who have subsequently been treated with tamoxifen (Esslimani-Sahla et al 2004, Fleming et al 2004, Gruvberger-Saal et al 2007. Other studies have, however, found that high vs low expression of ERb-like proteins have either no (Esslimani-Sahla et al 2004, Miller et al 2006, Skliris et al 2006, Honma et al 2008, Shaaban et al 2008 or poor (Saji et al 2002a,b, O'Neill et al 2004, Novelli et al 2008, Shaaban et al 2008 prognostic value in breast cancer.…”
Section: Clinical Correlation Studies Supporting the Bi-faceted Role mentioning
confidence: 99%
“…Rapid, non-genomic activities of estrogen are thought to be mediated by ERs localized to the plasma membrane on some target cells (Levin & Pietras 2008). With respect to differential subcellular localization of ERb-like proteins, extranuclear vs nuclear localization has been reported to provide differential prognostic information at least in breast cancer in vivo (Shaaban et al 2008. It is likely that ERb located in mitochondria and identified to interact with several mitochondrial proteins ) may have a dual role in mediating tamoxifeninduced apoptosis through increased ROS (Razandi et al 2012).…”
Section: Endocrine-related Cancermentioning
confidence: 99%